Non-destructive modeling using a drilling resistance tool to predict wood basic density of standing trees in a eucalypts plantation in North Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Singh KP, Siregar IZ, Abad JIM, Karlinasari L. 2022. Non-destructive modeling using a drilling resistance tool to predict wood basic density of standing trees in a eucalypts plantation in North Sumatra, Indonesia. Biodiversitas 23: 6218-6226. Eucalypts are globally selected as the main tree species for pulp and paper industries owing to their good potential growth and wood traits. Wood basic density, which is related to wood biomass yield, is one of the most important wood traits for pulp production and has become a focus in the tree improvement program. Evaluation of this trait in the field is needed to efficiently develop tree improvement programs. The aims of this study were to determine the distribution of basic density in the vertical direction of standing trees, including Eucalyptus grandis, Eucalyptus urophylla, and E. grandis × E. urophylla hybrid (commonly called “urograndis”), and to develop a model for predicting wood basic density using micro-drilling resistance tools of ResistographÒ. The results showed that basic density traits varied within individual trees and within and between species. Average whole tree basic wood densities of 379.9 kg/m3, 400.5 kg/m3, and 440.6 kg/m3 were found for E. grandis, hybrid urograndis, and E. urophylla at 44 months old, respectively. The model developed had a good correlation for predicting wood basic density at 1.3 m height and whole tree basic density, with the R2 for model calibration ranging from 0.52 to 0.76 for 1.3 m wood basic density prediction and from 0.62 to 0.79 for whole tree wood basic density. This study found that the three species of eucalyptus could be used to create a combined model for predicting wood basic density that could be used for each individual species. The model for single and multiple species had a good validation with R2 from 0.51 to 0.72.